A QLED device and a preparation method of the QLED device
Patent Information
- Application Number
- CN202110747433.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-02
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2041-07-02
AI Technical Summary
但无论是在器件效率还是器件工作稳定性等基本器件性能参数上还有相当大的差距,器件的寿命一直是限制其商业化应用最关键问题,其中发光层和电子传输层的稳定性又是影响寿命的关键因素
[0025]本发明提供的QLED器件,包括依次叠层设置的阴极、电子传输层、量子点发光层、以及阳极,其中,所述电子传输层和量子点发光层中至少一者的材料当中包括抗氧化剂。所述抗氧化剂可以防止量子点量子效率的降低,还能防止氧自由基的产生吸附在材料表面从而影响器件的效率,可以有效提高器件性能以及使用寿命。制备方法上只需在现有的QLED器件的制备方法的基础上,在电子传输层或量子点发光层的材料溶液内添加抗氧化剂即可,可通过多种方式沉积获得相应叠层。该制备工艺简单可控,有利于规模化生产应用。
Smart Images

Figure CN115568239B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of optoelectronic devices, and more specifically to a QLED device and a method for fabricating a QLED device. Background Technology
[0002] Quantum dots are nanocrystals with radii smaller than or close to the exciton Bohr radius, typically ranging from 1 to 20 nm in size. The significant quantum confinement effect endows quantum dots with numerous unique nanoscale properties: emission wavelength can be tunable by controlling particle size; narrow spectral linewidth; broad absorption spectrum; high color purity; high electron mobility; good photostability; good biocompatibility; and the ability to be used in flexible displays. These advantages have led to their widespread application in fields such as light-emitting displays, photovoltaic solar energy, and biolabeling.
[0003] Since the first quantum dot light-emitting diode (QLED) was fabricated in 1994, significant progress has been made in over 20 years in terms of material synthesis, device fabrication, and the mechanism of light emission. However, there are still considerable gaps in fundamental device performance parameters such as device efficiency and operational stability. Device lifetime remains the most critical issue limiting its commercial application, with the stability of the light-emitting layer and electron transport layer being key factors affecting lifetime.
[0004] Therefore, it is necessary to provide a QLED device and a method for fabricating a QLED device to solve the above problems. Summary of the Invention
[0005] The purpose of this invention is to provide a QLED device and a method for fabricating a QLED device, so as to improve the efficiency of QLED devices.
[0006] To achieve the above-mentioned objectives, the technical solution adopted by the present invention is as follows:
[0007] The present invention provides a QLED device, comprising an anode, a light-emitting layer, an electron transport layer, and a cathode stacked together, wherein at least one of the light-emitting layer and the electron transport layer comprises an antioxidant in its material.
[0008] Optionally, the antioxidant is selected from one or more of butylated hydroxytoluene, antioxidant 1010, antioxidant 1076, antioxidant 168, vitamin C, vitamin A, vitamin E, tea polyphenols, ethoxyquinoline, ethoxyquin, butylated hydroxyanisole, tert-butylhydroquinone, and propyl gallate.
[0009] Optionally, the antioxidant in the light-emitting layer or the electron transport layer has a molar fraction ranging from 0.1% to 20%.
[0010] Optionally, the material of the light-emitting layer may further include quantum dots, which are selected from one or more of group II-VI compound semiconductor quantum dots, group III-V compound semiconductor quantum dots, group I-III-VI compound semiconductor quantum dots, and perovskite quantum dots.
[0011] Optionally, the quantum dot is a core-shell quantum dot.
[0012] Optionally, the material of the electron transport layer may further include an inorganic oxide semiconductor, wherein the inorganic oxide semiconductor is selected from one or more of ZnO, SnO2, TiO2, Mg, or Al-doped ZnO.
[0013] Optionally, the material of the light-emitting layer is composed of antioxidants and quantum dots; or the material of the electron transport layer is composed of antioxidants and inorganic oxide semiconductors.
[0014] Accordingly, a method for fabricating a QLED device is characterized by comprising the following steps:
[0015] A light-emitting layer material solution and an electron transport layer material solution are provided respectively;
[0016] The light-emitting layer material solution is deposited on the anode substrate to form the light-emitting layer;
[0017] The electron transport layer material solution is deposited on the light-emitting layer to form the electron transport layer;
[0018] Alternatively, the electron transport layer material solution can be deposited on the cathode substrate to form the electron transport layer;
[0019] The light-emitting layer material solution is deposited on the electron transport layer to form the light-emitting layer;
[0020] At least one of the light-emitting layer material solution and the electron transport layer material solution includes an antioxidant.
[0021] Optionally, the light-emitting layer material solution further includes quantum dots dispersed in alkane-based organic reagents; the electron transport layer material solution further includes inorganic oxide semiconductors dispersed in alcohol-based organic reagents.
[0022] Optionally, the antioxidant has a mass fraction of 1%-50% based on the total mass of the quantum dots dispersed in the alkane organic reagent or the inorganic oxide semiconductor dispersed in the alcohol organic reagent.
[0023] Optionally, the concentration of the quantum dots is 10–40 mg / mL.
[0024] Beneficial effects:
[0025] The QLED device provided by this invention includes a cathode, an electron transport layer, a quantum dot light-emitting layer, and an anode, which are sequentially stacked. At least one of the electron transport layer and the quantum dot light-emitting layer comprises an antioxidant. The antioxidant can prevent the reduction of quantum dot efficiency and prevent the generation and adsorption of oxygen free radicals on the material surface, thus affecting the device efficiency and effectively improving device performance and lifespan. The fabrication method simply involves adding an antioxidant to the material solution of the electron transport layer or the quantum dot light-emitting layer, based on existing QLED device fabrication methods. The corresponding stacked layers can be obtained through various deposition methods. This fabrication process is simple and controllable, facilitating large-scale production and application. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 This is a schematic diagram of an inverted QLED device provided in Embodiment 1 of this application; Attached image description:
[0029] Substrate 110; Cathode 120; Electron transport layer 130; Light-emitting layer 140; Hole transport layer 150; Hole injection layer 160; Anode 170. Detailed Implementation
[0030] To make the technical problems, solutions, and effects of this invention clearer, the technical solutions in the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0031] This application provides a QLED device and a method for fabricating a QLED device. Detailed descriptions are provided below. It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of embodiments. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a rigid limitation on the scope of the invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single digits within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Additionally, whenever a numerical range is indicated herein, it means including any referenced number (fraction or integer) within the indicated range.
[0032] This invention provides a QLED device, comprising an anode, a light-emitting layer, an electron transport layer, and a cathode stacked together, wherein at least one of the light-emitting layer and the electron transport layer comprises an antioxidant. The antioxidant prevents oxidizing substances such as oxygen or oxygen free radicals in the air from damaging the material of the light-emitting layer or the electron transport layer. This improves the oxidation resistance of the QLED device and extends its lifespan.
[0033] Optionally, the antioxidant is one or more of butylated hydroxytoluene (BHT), antioxidant 1010 (Irganox1010), antioxidant 1076 (Irganox1076), antioxidant 168 (Irgafos168), vitamin C, vitamin A, vitamin E, tea polyphenols, ethoxyquinoline, ethoxyquin (EMQ), butylated hydroxyanisole (BHA), tert-butylhydroquinone (TBHQ), or propyl gallate (PG).
[0034] The antioxidant in the light-emitting layer and / or the electron transport layer has a molar fraction ranging from 0.1% to 20%. Within this range, the antioxidant properties of the light-emitting layer and the electron transport layer are guaranteed, while the addition of the antioxidant does not affect the performance of the light-emitting layer and the electron transport layer.
[0035] The luminescent layer material also includes quantum dots, selected from one or more of group II-VI compound semiconductor quantum dots, group III-V compound semiconductor quantum dots, group I-III-VI compound semiconductor quantum dots, or perovskite quantum dots. Group II elements include, but are not limited to, Zn, Cd, and Hg; group VI elements include, but are not limited to, O, S, Se, Te, Po, and Lv; group III elements include, but are not limited to, Ga, In, and Pb; and group V elements include, but are not limited to, As and P. Optionally, the quantum dots are core-shell structured quantum dots. Coating with an organic or inorganic shell can effectively improve the fluorescence properties of the quantum dots, increase quantum efficiency, and enhance the photoelectric effect.
[0036] Optionally, the material of the electron transport layer may also include inorganic oxide semiconductors, wherein the inorganic oxide semiconductor is one or more of ZnO, SnO2, TiO2, and Mg or Al doped ZnO.
[0037] QLED devices can be either upright or inverted. Preferably, a QLED device also includes a substrate, with the anode or cathode disposed on the substrate. There are no specific restrictions on the choice of substrate material; rigid substrates or flexible substrates can be used. Rigid substrates include, but are not limited to, glass plates, while flexible substrates include, but are not limited to, PET substrates.
[0038] QLED devices can be top-emitting or bottom-emitting devices. To better understand this solution, a bottom-emitting QLED device is provided here, wherein the anode or cathode material disposed on the substrate is a transparent material, such as a doped metal oxide, including but not limited to one or more of indium-doped tin oxide (ITO), fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), indium-doped zinc oxide (IZO), magnesium-doped zinc oxide (MZO), and aluminum-doped magnesium oxide (AMO). It can also be a composite electrode selected from doped or undoped transparent metal oxides sandwiching metal, including but not limited to one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, and ZnS / Al / ZnS.
[0039] To better understand this solution, a top-emitting QLED device is also provided, wherein the anode or cathode material disposed on the substrate is an opaque material, such as a metal or alloy, including but not limited to Ag, Al, and Au.
[0040] The QLED device provided by this invention may further include a hole functional layer disposed between the anode and the light-emitting layer. The hole functional layer includes at least one of a hole transport layer and a hole injection layer. The hole functional layer can effectively improve the charge transport function.
[0041] The material of the hole transport layer is C 38 H 28 N2, or 4,4'-bis(9H-carbazol-9-yl)-2,2'-dimethylbiphenyl, commonly abbreviated as CDBP; C 36 H 24 N2, or 4,4′-N,N′-dicarbazole biphenyl, is commonly abbreviated as CBP; C 15 H 16 N2O2, or N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, is commonly abbreviated as NPB; C 54 H 36 N4, or tris(4-(9-carbazolyl)phenyl)amine, is commonly represented by the abbreviation TCTA as one or more of these substances.
[0042] The hole injection layer 160 is made of one or more of the following materials: 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazabenzophenanthrene (HAT-CN), molybdenum trioxide (MoO3), tungsten trioxide (WO3), vanadium pentoxide (V2O5), and tantalum pentoxide (Ta2O5). The hole injection layer can improve hole injection efficiency and mobility, balance the mobility between holes and electrons, and greatly increase the probability of carrier radiative recombination, thereby improving the brightness and luminous efficiency of QLEDs.
[0043] Accordingly, to better understand this solution, a method for fabricating an upright QLED device is provided, comprising:
[0044] Step S110: Provide the light-emitting layer material solution and the electron transport layer material solution respectively;
[0045] Step S210: Deposit a light-emitting layer material solution on the anode substrate to form a light-emitting layer;
[0046] Step S310: Deposit an electron transport layer material solution on the light-emitting layer to form an electron transport layer;
[0047] Alternatively, a method for fabricating an inverted QLED device is provided, comprising:
[0048] Step S120: Provide the light-emitting layer material solution and the electron transport layer material solution respectively;
[0049] Step S220: An electron transport layer material solution is applied to the cathode substrate to form an electron transport layer;
[0050] Step S320: Deposit a light-emitting layer material solution on the electron transport layer to form a light-emitting layer;
[0051] In this embodiment, at least one of the light-emitting layer material solution and the electron transport layer material solution includes an antioxidant. Adding an antioxidant to the light-emitting layer material solution prevents a decrease in the quantum efficiency of the quantum dots, while adding an antioxidant to the electron transport layer material solution prevents the generation of oxygen free radicals that adsorb onto the surface of inorganic oxide semiconductors such as ZnO, thereby affecting the device efficiency. Antioxidants can improve the stability of the electron transport layer or light-emitting layer material solutions, thus improving device performance and lifespan.
[0052] The light-emitting layer material solution also includes quantum dots dispersed in alkane-based organic reagents; the electron transport layer material solution also includes inorganic oxide semiconductors dispersed in alcohol-based organic reagents. Using quantum dots as the light-emitting layer material, the prepared QLED devices exhibit good photostability and, compared to traditional phosphors, can significantly improve the color gamut of the display devices.
[0053] The concentration of quantum dots dispersed in alkane-based organic reagents is 5 mg / mL to 60 mg / mL, preferably 10–40 mg / mL. The solvent in the quantum dot solution can be, for example, n-octane, prepared by dissolving the quantum dots in n-octane. If the solution concentration is too low, the quantum dot emitting layer in the device will be too thin, resulting in weak device brightness. If the concentration of the quantum dot solution is too high, the quantum dot emitting layer will be too thick, increasing the internal resistance of the device and hindering performance improvement. Preferably, the particle size range of the quantum dots is 8 to 15 nanometers (nm), such as 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, etc. If the particle size of the quantum dots is too small, the film-forming properties of the quantum dot material deteriorate, and the energy resonance transfer effect between quantum dot particles becomes significant, which is detrimental to the application of the material. If the particle size of the quantum dots is too large, the quantum effect of the quantum dot material weakens, leading to a decrease in the photoelectric performance of the material. The thickness of the formed quantum dot emitting layer is 5–50 nm.
[0054] The concentration of inorganic oxide semiconductors dispersed in alcohol-based organic reagents ranges from 10 mg / mL to 50 mg / mL. If the concentration of the electron transport material is too low, the electron transport layer in the optoelectronic device will be too thin; if the concentration is too high, the electron transport layer will be too thick. Both excessively thin and excessively thick electron transport layers can lead to an electron-hole imbalance within the device, resulting in degraded device performance. The thickness of the formed electron transport layer is 5-100 nm.
[0055] The antioxidant has a mass fraction of 1%-50% based on the total mass of quantum dots dispersed in alkane-based organic reagents or inorganic oxide semiconductors dispersed in alcohol-based organic reagents, preferably 5%-20%. Within this range, the light-emitting layer material solution and the electron transport layer material solution can fully improve the antioxidant performance, and the stability after film formation is also improved. Furthermore, the impact on the light-emitting performance of the light-emitting layer and the transport performance of the electron transport layer is negligible, and the lifetime of the QLED device prepared by solution can be effectively extended.
[0056] Optionally, the deposition is selected from spin coating, inkjet printing, and blade coating. To better understand this solution, a specific operation of step S210 or S220 is provided, including: placing the ITO substrate in a glove box, spin coating a film using a prepared light-emitting layer or electron transport layer material solution; controlling the film thickness by adjusting the solution concentration, spin coating speed, and spin coating time; and then thermally annealing the thickness at an appropriate temperature. In optoelectronic device fabrication, spin coating has the advantages of mild process conditions, simple operation, energy saving, and environmental friendliness. It also offers advantages such as high carrier mobility and precise thickness in the fabrication of optoelectronic devices. Currently, spin coating is the most commonly used method for fabricating quantum dot light-emitting diodes.
[0057] The spin coating speed can be from 1000 rpm to 6000 rpm, and more preferably from 2000 rpm to 4000 rpm. If the spin coating speed is too low, the hole transport layer will be too thick; if the spin coating speed is too high, the hole transport layer will be too thin. Both excessively thin and excessively thick hole transport layers will lead to an imbalance of electrons and holes inside the quantum dot device, resulting in a deterioration in device performance.
[0058] The spin coating time can be from 10s to 100s, and more preferably from 30s to 60s. If the spin coating time is too short, the hole transport layer will contain a large amount of unevaporated solvent, resulting in poor film formation of the electron transport layer during the subsequent drying process. If the spin coating time is too long, the production efficiency will decrease.
[0059] After spin-coating the composite material solution, heat treatment can be performed. The heat treatment temperature range is 50°C to 150°C, more preferably 80°C to 120°C. The purpose of heat treatment is to remove solvent molecules from the hole transport layer and avoid residual solvent affecting the film formation effect. If the heat treatment temperature is too low, the solvent molecules will be difficult to remove completely; if the heat treatment temperature is too high, the functional layer film structure of the quantum dot device will be easily damaged, affecting the photoelectric performance of the device. In some embodiments of this application, the heat treatment time ranges from 10 min to 60 min. If the heat treatment time is too short, the solvent molecules will be difficult to remove completely; if the heat treatment time is too long, the functional layer film structure of the quantum dot device will be easily damaged, affecting the photoelectric performance of the device.
[0060] To better understand this solution, a method for fabricating a bottom-emission QLED device is provided, including steps S110-S310 or S120-S320. Between steps S110 and S210 or between steps S120 and S220, a pretreatment step is also included: ultrasonically cleaning the transparent anode substrate or cathode substrate in a cleaning reagent and then drying it. Specifically, the substrate is ultrasonically cleaned in detergent, deionized water, acetone, ethanol and / or deionized water for 2-30 minutes each time.
[0061] To better understand this solution, a method for fabricating a top-emitting QLED device is provided, including steps S110-S310 or S120-S320. Between steps S110 and S210 or between steps S120 and S220, an anode or cathode deposition step is also included: depositing a non-transparent anode material solution or cathode material solution on a substrate to form an anode or cathode with a thickness of 5-300 nm, preferably 50-150 nm. Physical deposition methods include, but are not limited to, evaporation and sputtering.
[0062] QLED devices can incorporate a hole functional layer to improve charge transport performance. Therefore, the fabrication method of QLED devices further includes the step of depositing at least one hole injection layer or hole transport layer using a physical deposition method. The hole injection layer and hole transport layer conform to the conventional QLED structure. The deposition method for the hole injection layer or hole transport layer is not limited to physical deposition methods, as long as they meet the requirements. These methods include, but are not limited to, thermal evaporation deposition, electron beam evaporation deposition, magnetron sputtering, multi-arc ion deposition, physical vapor deposition, atomic layer deposition, and pulsed laser deposition. Further, after depositing the hole injection layer or hole transport layer, heat treatment is performed to remove the solvent from each layer. For the hole injection layer, the oxide prepared using a metal precursor can be annealed and converted into a metal oxide through the heat treatment. The thickness of the hole transport layer is 5-100 nm, preferably 25-70 nm. The thickness of the hole injection layer is 1-50 nm, preferably 5-20 nm. Both excessively thin and excessively thick hole functional layers can lead to an electron-hole imbalance within the device, resulting in degraded device performance. The fabrication method of QLEDs involves sequentially depositing a hole transport layer and a hole injection layer on the light-emitting layer, and then fabricating an anode on the hole injection layer.
[0063] To better understand this solution, specific embodiments 1-5 and comparative example 1 are provided here to further illustrate this solution in detail.
[0064] Example 1
[0065] An inverted QLED device comprising an antioxidant in an electron transport layer material includes a substrate 110, a cathode 120, an electron transport layer 130, a light-emitting layer 140, a hole transport layer 150, a hole injection layer 160, and an anode 170 stacked together. The substrate 110 is made of glass, the cathode 120 is made of ITO glass substrate, the electron transport layer 130 is made of MgZnO+BHA, the light-emitting layer is made of CdSe / ZnS, the hole transport layer 150 is made of CBP, the hole injection layer 160 is made of MoO3, and the anode 170 is made of Ag.
[0066] Accordingly, this embodiment also provides a method for fabricating an inverted QLED device, including:
[0067] Provide solutions for light-emitting layer and electron transport layer materials;
[0068] The ITO glass substrate was placed in detergent, deionized water, acetone, ethanol and deionized water in sequence, and ultrasonicated for 15 minutes each time, and then dried at 100°C.
[0069] An electron transport layer with a thickness of 50 nm was formed on the treated ITO substrate by spin-coating an electron transport layer material solution in a glove box. The electron transport layer material solution included MgZnO dispersed in ethanol, with a Mg doping ratio of 5% and a concentration of 20 mg / mL, and BHA with a mass fraction of 5% based on the mass of the MgZnO ethanol solution. The substrate was then annealed in a glove box at 100 °C for 10 min.
[0070] A light-emitting layer material solution was spin-coated onto the cooled sheet to form a light-emitting layer with a thickness of 25 nm. The light-emitting layer material solution included CdSe / ZnS core-shell structured quantum dots dispersed in n-octane at a concentration of 15 mg / mL. Then, the sheet was annealed at a temperature of 100 °C for 10 min.
[0071] The cooled substrate is transferred to an evaporation machine to deposit CBP material to form a 50nm thick hole transport layer;
[0072] MoO3 was evaporated onto the treated substrate to form a hole injection layer with a thickness of 10 nm.
[0073] The processed substrate is transferred to an evaporation machine to deposit an anode material with a thickness of 100 nm to form an anode layer, wherein the anode material is Ag.
[0074] Example 2
[0075] An inverted QLED device comprising an antioxidant in its light-emitting layer material includes a substrate, a cathode, an electron transport layer, a light-emitting layer, a hole transport layer, a hole injection layer, and an anode, all stacked together. The substrate material is a glass sheet; the cathode material is an ITO glass substrate; the electron transport layer material is MgZnO; the light-emitting layer material is CdSe / ZnS+BHA; the hole transport layer material is CBP; the hole injection layer material is MoO3; and the anode material is Ag. In the light-emitting layer, the mass fraction of BHA is 10% based on the total mass of the CdSe / ZnS core-shell quantum dots.
[0076] Accordingly, this embodiment also provides a method for fabricating an inverted QLED device, including:
[0077] Provide solutions for light-emitting layer and electron transport layer materials;
[0078] The ITO glass substrate was placed in detergent, deionized water, acetone, ethanol and deionized water in sequence, and ultrasonicated for 15 minutes each time, and then dried at 100°C.
[0079] An electron transport layer with a thickness of 50 nm was formed on the treated ITO substrate by spin-coating an electron transport layer material solution in a glove box. The electron transport layer material solution included MgZnO dispersed in ethanol, with a Mg doping ratio of 5% and a concentration of 20 mg / mL. Then, the substrate was annealed in a glove box at 100 °C for 10 min.
[0080] A light-emitting layer material solution was spin-coated onto the cooled sheet to form a light-emitting layer with a thickness of 25 nm. The light-emitting layer material solution included CdSe / ZnS core-shell quantum dots dispersed in n-octane at a concentration of 15 mg / mL, and BHA with a mass fraction of 10% based on the total mass of the CdSe / ZnS core-shell quantum dots dispersed in n-octane. The sheet was then annealed at a temperature of 100 °C for 10 min.
[0081] The cooled substrate is transferred to an evaporation machine to deposit CBP material to form a 50nm thick hole transport layer;
[0082] MoO3 was evaporated onto the treated substrate to form a hole injection layer with a thickness of 10 nm.
[0083] The processed substrate is transferred to an evaporation machine to deposit an anode material with a thickness of 100 nm to form an anode layer, wherein the anode material is Ag.
[0084] Example 3
[0085] An inverted QLED device in which both the electron transport layer material and the light-emitting layer material include antioxidants includes a substrate, a cathode, an electron transport layer, a light-emitting layer, a hole transport layer, a hole injection layer, and an anode stacked together. The substrate material is a glass sheet, the cathode material is an ITO glass substrate, the electron transport layer material is MgZnO+BHA, the light-emitting layer material is CdSe / ZnS+BHA, the hole transport layer material is CBP, the hole injection layer material is MoO3, and the anode material is Ag. In the light-emitting layer, the mass fraction of BHA is 10% based on the total mass of the CdSe / ZnS core-shell quantum dots.
[0086] Accordingly, this embodiment also provides a method for fabricating an inverted QLED device, including:
[0087] Provide solutions for light-emitting layer and electron transport layer materials;
[0088] The ITO glass substrate was placed in detergent, deionized water, acetone, ethanol and deionized water in sequence, and ultrasonicated for 15 minutes each time, and then dried at 100°C.
[0089] An electron transport layer with a thickness of 50 nm was formed on the treated ITO substrate by spin-coating an electron transport layer material solution in a glove box. The electron transport layer material solution included MgZnO dispersed in ethanol, with a Mg doping ratio of 5% and a concentration of 20 mg / mL, and BHA with a mass fraction of 5% based on the mass of the MgZnO ethanol solution. The substrate was then annealed in a glove box at 100 °C for 10 min.
[0090] A light-emitting layer material solution was spin-coated onto the cooled sheet to form a light-emitting layer with a thickness of 25 nm. The light-emitting layer material solution included CdSe / ZnS core-shell quantum dots dispersed in n-octane at a concentration of 15 mg / mL, and BHA with a mass fraction of 10% based on the total mass of the CdSe / ZnS core-shell quantum dots dispersed in n-octane. The sheet was then annealed at a temperature of 100 °C for 10 min.
[0091] The cooled substrate is transferred to an evaporation machine to deposit CBP material to form a 50nm thick hole transport layer;
[0092] MoO3 was evaporated onto the treated substrate to form a hole injection layer with a thickness of 10 nm.
[0093] The processed substrate is transferred to an evaporation machine to deposit an anode material with a thickness of 100 nm to form an anode layer, wherein the anode material is Ag.
[0094] Example 4
[0095] An inverted QLED device comprising an antioxidant in its light-emitting layer material includes a substrate, a cathode, an electron transport layer, a light-emitting layer, a hole transport layer, a hole injection layer, and an anode, stacked together. The substrate material is a glass sheet; the cathode material is an ITO glass substrate; the electron transport layer material is MgZnO; the light-emitting layer material is CdSe+PG; the hole transport layer material is CBP; the hole injection layer material is MoO3; and the anode material is Ag. In the light-emitting layer, the mass fraction of PG, based on the total mass of the CdSe quantum dots, is 35%.
[0096] Accordingly, this embodiment also provides a method for fabricating an inverted QLED device, including:
[0097] Provide solutions for light-emitting layer and electron transport layer materials;
[0098] The ITO glass substrate was placed in detergent, deionized water, acetone, ethanol and deionized water in sequence, and ultrasonicated for 15 minutes each time, and then dried at 100°C.
[0099] An electron transport layer with a thickness of 85 nm was formed on the treated ITO substrate by spin-coating an electron transport layer material solution in a glove box. The electron transport layer material solution included MgZnO dispersed in methanol, with a Mg doping ratio of 5% and a concentration of 45 mg / mL. The substrate was then annealed in a glove box at 100 °C for 10 min.
[0100] A light-emitting layer material solution was spin-coated onto the cooled wafer to form a light-emitting layer with a thickness of 45 nm. The light-emitting layer material solution included CdSe quantum dots dispersed in n-pentane at a concentration of 35 mg / mL, and PG with a mass fraction of 35% based on the total mass of CdSe quantum dots dispersed in n-pentane. The wafer was then annealed at a temperature of 100 °C for 20 min.
[0101] The cooled substrate was transferred to an evaporation machine to deposit CBP material to form a 60nm thick hole transport layer;
[0102] MoO3 was evaporated onto the treated substrate to form a hole injection layer with a thickness of 20 nm.
[0103] The processed substrate is transferred to a vapor deposition machine to vapor deposit an anode material to form an anode layer with a thickness of 80 nm, wherein the anode material is Ag.
[0104] Example 5
[0105] An inverted QLED device in which both the electron transport layer material and the light-emitting layer material include antioxidants includes a substrate, a cathode, an electron transport layer, a light-emitting layer, a hole transport layer, a hole injection layer, and an anode stacked together. The substrate material is a glass sheet, the cathode material is an ITO glass substrate, the electron transport layer material is MgZnO+BHT, the light-emitting layer material is CdSe+Irganox1010, the hole transport layer material is CBP, the hole injection layer material is MoO3, and the anode material is Ag. The mass fraction of Irganox1010 is 40% based on the total mass of the CdSe quantum dots.
[0106] Accordingly, this embodiment also provides a method for fabricating an inverted QLED device, including:
[0107] Provide solutions for light-emitting layer and electron transport layer materials;
[0108] The ITO glass substrate was placed in detergent, deionized water, acetone, ethanol and deionized water in sequence, and ultrasonicated for 20 minutes each time, and then dried at 100°C.
[0109] An electron transport layer with a thickness of 20 nm was formed on the treated ITO substrate by spin-coating an electron transport layer material solution in a glove box. The electron transport layer material solution included MgZnO dispersed in propanol, with a Mg doping ratio of 5% and a concentration of 15 mg / mL, and BHT with a mass fraction of 25% based on the mass of the MgZnO ethanol solution. The substrate was then annealed in a glove box at 100 °C for 10 min.
[0110] A light-emitting layer material solution was spin-coated onto the cooled wafer to form a light-emitting layer with a thickness of 30 nm. The light-emitting layer material solution included CdSe quantum dots dispersed in n-octane at a concentration of 30 mg / mL, and Irganox 1010 with a mass fraction of 40% based on the total mass of CdSe quantum dots dispersed in n-octane. The wafer was then annealed at a temperature of 100 °C for 10 min.
[0111] The cooled substrate was transferred to an evaporation machine to deposit CBP material to form a 70nm thick hole transport layer;
[0112] MoO3 was evaporated onto the treated substrate to form a hole injection layer with a thickness of 30 nm.
[0113] The processed substrate is transferred to an evaporation machine to deposit an anode material with a thickness of 100 nm to form an anode layer, wherein the anode material is Ag.
[0114] Comparative Example 1
[0115] An inverted QLED device whose fabrication material does not contain antioxidants includes a substrate, a cathode, an electron transport layer, a light-emitting layer, a hole transport layer, a hole injection layer, and an anode stacked together. The substrate material is a glass sheet, the cathode material is an ITO glass substrate, the electron transport layer material is MgZnO, the light-emitting layer material is CdSe / ZnS, the hole transport layer material is CBP, the hole injection layer material is MoO3, and the anode material is Ag.
[0116] Accordingly, this embodiment also provides a method for fabricating an inverted QLED device, including:
[0117] Provide solutions for light-emitting layer and electron transport layer materials;
[0118] The ITO glass substrate was placed in detergent, deionized water, acetone, ethanol and deionized water in sequence, and ultrasonicated for 15 minutes each time, and then dried at 100°C.
[0119] An electron transport layer with a thickness of 50 nm was formed on the treated ITO substrate by spin-coating an electron transport layer material solution in a glove box. The electron transport layer material solution included MgZnO dispersed in ethanol, with a Mg doping ratio of 5% and a concentration of 20 mg / mL. Then, the substrate was annealed in a glove box at 100 °C for 10 min.
[0120] A light-emitting layer material solution was spin-coated onto the cooled sheet to form a light-emitting layer with a thickness of 25 nm. The light-emitting layer material solution included CdSe / ZnS core-shell structured quantum dots dispersed in n-octane at a concentration of 15 mg / mL. Then, the sheet was annealed at a temperature of 100 °C for 10 min.
[0121] The cooled substrate is transferred to an evaporation machine to deposit CBP material to form a 50nm thick hole transport layer;
[0122] MoO3 was evaporated onto the treated substrate to form a hole injection layer with a thickness of 10 nm.
[0123] The processed substrate is transferred to an evaporation machine to deposit an anode material with a thickness of 100 nm to form an anode layer, wherein the anode material is Ag.
[0124] Experimental Example 1: Maximum current efficiency of QLED devices in different embodiments and comparative examples. Current efficiency refers to the ratio of the amount of substance actually deposited or dissolved on the electrode during electrolysis to the amount of precipitation or dissolution calculated theoretically.
[0125] Table 1 Efficiency of different QLED devices
[0126] <![CDATA[CE max (Cd / A)]]> 17.4 18.5 22.7 15.2
[0127] The results above show that, for Examples 1, 2, and 3 and Comparative Example 1, the CE values of Experimental Examples 1, 2, and 3 are significantly different. max The (Cd / A) values were all significantly higher than those in Comparative Example 1, especially in Example 3, where the CE values were significantly higher after adding antioxidants to both the electron transport layer material and the luminescent layer material. max The (Cd / A) value is higher than that of adding antioxidants alone to electron transport layer materials or light-emitting layer materials.
[0128] Experimental Example 2: Lifetime of different QLED devices, expressed by the T95 lifetime at 1000 nits. T95 represents the time it takes for the maximum brightness to decay to 95% manually. The T95 lifetime at 1000 nits is the time it takes for the QLED device to decay to 95%, which is about 950 nits.
[0129] Table 2 Lifetime of different QLED devices
[0130] T95@1000nit(h) 1329 1851 2825 856
[0131] The results above show that the T95@1000nit values of Examples 1, 2, 3 and Comparative Example 1 are significantly higher than those of Comparative Example 1. In particular, in Example 3, the T95@1000nit(h) value is higher when antioxidants are added to both the electron transport layer material and the light-emitting layer material at the same time than when antioxidants are added to either the electron transport layer material or the light-emitting layer material alone.
[0132] In summary, this invention, by adding an antioxidant to at least one of the materials of the electron transport layer and the quantum dot emitting layer, effectively prevents the reduction of quantum dot quantum efficiency and prevents the generation and adsorption of oxygen free radicals on the material surface, thereby affecting device efficiency. This significantly improves device performance and lifespan. The fabrication method simply involves adding an antioxidant to the material solution of the electron transport layer or the quantum dot emitting layer, building upon existing QLED device fabrication methods. The corresponding stack can be obtained through deposition in various ways. This fabrication process is simple and controllable, facilitating large-scale production and application.
[0133] The present invention provides a detailed description of a QLED device and its fabrication method. Specific examples have been used to illustrate the principle and implementation scheme of the present invention. The description of the above embodiments is only for the purpose of helping to understand the method and core idea of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be considered as the scope of protection of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A QLED device, characterized in that, The device includes an anode, a light-emitting layer, an electron transport layer, and a cathode stacked together. The light-emitting layer is made of an antioxidant and quantum dots, and the electron transport layer is made of an inorganic oxide semiconductor and an antioxidant. The inorganic oxide semiconductor is selected from one or more of ZnO, SnO2, TiO2, Mg, or Al-doped ZnO. The antioxidant is selected from one or more of vitamin C, vitamin A, vitamin E, tea polyphenols, butylated hydroxyanisole, tert-butylhydroquinone, and propyl gallate.
2. The QLED device according to claim 1, characterized in that, The antioxidant has a molar fraction in the light-emitting layer and / or the electron transport layer ranging from 0.1% to 20%.
3. The QLED device according to claim 1, characterized in that, The quantum dots are selected from one or more of the following: quantum dots of group II-VI compound semiconductors, quantum dots of group III-V compound semiconductors, quantum dots of group I-III-VI compound semiconductors, and perovskite quantum dots.
4. The QLED device according to claim 3, characterized in that, The quantum dot is a core-shell structured quantum dot.
5. The QLED device according to claims 1-4, characterized in that, The material of the light-emitting layer is composed of antioxidants and quantum dots; or The electron transport layer is composed of antioxidants and inorganic oxide semiconductors.
6. A method for fabricating a QLED device, characterized in that, Including the following steps: A solution for the luminescent layer material and a solution for the electron transport layer material are provided respectively; The light-emitting layer material solution is deposited on the anode substrate to form the light-emitting layer; The electron transport layer material solution is deposited on the light-emitting layer to form the electron transport layer; Alternatively, the electron transport layer material solution can be deposited on the cathode substrate to form the electron transport layer; The light-emitting layer material solution is deposited on the electron transport layer to form the light-emitting layer; The light-emitting layer material solution includes an antioxidant and quantum dots, and the electron transport layer material solution includes an inorganic oxide semiconductor and an antioxidant. The inorganic oxide semiconductor is selected from one or more of ZnO, SnO2, TiO2, Mg, or Al-doped ZnO. The antioxidant is selected from one or more of vitamin C, vitamin A, vitamin E, tea polyphenols, butylated hydroxyanisole, tert-butylhydroquinone, and propyl gallate.
7. The method for fabricating a QLED device as described in claim 6, characterized in that, The quantum dots are dispersed in alkane-based organic reagents; the inorganic oxide semiconductors are dispersed in alcohol-based organic reagents.
8. The method for fabricating a QLED device as described in claim 7, characterized in that, The antioxidant has a mass fraction of 1%-50% based on the total mass of the quantum dots dispersed in alkane organic reagents or the inorganic oxide semiconductor dispersed in alcohol organic reagents.
9. The method for fabricating a QLED device as described in claim 7, characterized in that, The concentration of the quantum dots is 10~40 mg / mL.
Citation Information
Patent Citations
Organic electroluminescent device and preparation method thereof, and display panel
CN110459687A
Discharge liquid, discharge liquid set, thin film pattern forming method, thin film, light emitting element, image display device, and electronic equipment
JP2010009995A
Organic Electroluminescence Display Device ComprisingAnti-oxidants
KR1020050052288A